Pemikiran Dakwah Siyasi (Deskripsi Pandangan Syahrur mengenai Hubungan Syura, Demokrasi dan Negara dalam Islam - Haris, Iir Abdul (Jurnal Ilmu Dakwah, 2009)
Secularistic model that framed modern democratization can be a truthfully historical Islamic state model. Islamic indication of modern democratization such as emancipation and nationalism so its existence indemnity bond, and so syura mechanism that constitutes essential of democracyâs relative in line with Islamic state principle. Muhammad Syahrur argues the assumption that refuse secularistics model is taken by moslem society. Because according to Syahrur terminology in reality natural political process happening on seculars circle at the end will come up with political ideal goal that is hungered by all people.